Novel function of adrenocorticotropic hormone in the stimulation of vascular endothelial growth factor release in healthy children and adolescents: a proof-of-concept study - Ryan Heksch; Sasigarn Bowden; Robert Hoffman (Korean Society of Pediatric Endocrinology, 2021)
Purpose To assess the effect of adrenocorticotropic hormone (ACTH) on plasma vascular endothelial growth factor (VEGF) levels in healthy children and adolescents and to inform future work on the effects of ACTH on VEGF in bone. Methods An Institutional Review Board-approved prospective study of 10 healthy subjects, ages 9-17, was conducted to assess the effect of ACTH on plasma VEGF levels. VEGF levels were collected at baseline and every 30 minutes for 3 hours. Cosyntropin (a synthetic ACTH analogue) was administered at a low-dose (1 μg) given at t=0 minutes and a high-dose (250 μg) given at t=60 minutes. A Friedman test was performed comparing baseline to peak VEGF levels after stimulation with low-dose and high-dose cosyntropin. Results Peak plasma VEGF levels significantly increased after high-dose cosyntropin compared with baseline (P=0.042). Peak plasma VEGF levels did not significantly increase after low-dose cosyntropin compared to baseline. Conclusions To our knowledge, this is the first study to demonstrate that ACTH administration causes a significant increase in plasma VEGF levels in humans. This finding may have important implications in the protective effects of ACTH on bone. Decreased bone mineral density and adrenal suppression are common side effects of glucocorticoid use in pediatrics. VEGF increases vascularity and may play a role in reducing glucocorticoid-induced bone disease. Animal studies have shown that ACTH stimulates release of VEGF in osteoblasts, though this effect has yet to be evaluated in humans.